2002
DOI: 10.1074/jbc.m205500200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of a Novel Mitochondrial Metalloprotease (PreP) That Degrades Targeting Presequences in Plants

Abstract: Most of the nuclear encoded mitochondrial precursor proteins contain an N-terminal extension called the presequence that carries targeting information and that is cleaved off after import into mitochondria. The presequences are amphiphilic, positively charged, membrane-interacting peptides with a propensity to form ␣-helices. Here we have investigated the proteolysis of the presequences that have been cleaved off inside mitochondria. A presequence derived from the overexpressed F 1 ␤ subunit of the ATP synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 80 publications
1
87
0
Order By: Relevance
“…17). PreP initially was identified in plant mitochondria as the protease responsible for the degradation of the presequence of the ATPase beta subunit (pF 1 β) and the chloroplastic transit peptide of the small subunit of ribulose-1,5-bisphosphate carboxylase oxygenase (18,19). Consistent with this result, A. thaliana PreP (AtPreP) was shown to have a dual localization in mitochondrial matrix and chloroplastic stroma (18,20).…”
supporting
confidence: 66%
“…17). PreP initially was identified in plant mitochondria as the protease responsible for the degradation of the presequence of the ATPase beta subunit (pF 1 β) and the chloroplastic transit peptide of the small subunit of ribulose-1,5-bisphosphate carboxylase oxygenase (18,19). Consistent with this result, A. thaliana PreP (AtPreP) was shown to have a dual localization in mitochondrial matrix and chloroplastic stroma (18,20).…”
supporting
confidence: 66%
“…However, a complete proteolytic breakdown of mitochondrial proteins to amino acid residues has already been observed in early studies pointing to the presence of oligopeptidases in mitochondria (21). Until now only two ATP-independent mitochondrial oligopeptidases have been identified, a thimet oligopeptidase localized in the intermembrane space of yeast and human mitochondria (22,23) and the presequencedegrading metallopeptidase PreP in plant mitochondria (24). Other known peptidases act as processing enzymes cleaving off mitochondrial targeting sequences from newly imported preproteins (25).…”
mentioning
confidence: 99%
“…The isolated targeting signal of a mitochondrial precursor remained stable in the presence of MPP (36). When a targeting signal was produced during processing in the mitochondrial matrix, however, its rapid hydrolysis by a novel peptidase occurred without detectable intermediates (37). However, in human ER membranes and E. coli inner membranes, proteolytic enzymes have been identified that internally cleave targeting signals after they have been removed from precursor proteins by signal peptidases (38,39).…”
Section: Discussionmentioning
confidence: 99%